OUR UNITIAL EXPERIMENTS IN REPLACEMENT EXTENSIVE DEFECTS OF BONE TISSUE OF SHINBONE WITH A NEW DEVICE - Majidov К.SH, Kholkhodzhaev F.I, (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA'LIMNING INNOVATSION YO'NALISHLARI, 2025)
The scientific work presents initial experiments on the replacement of widespread defects of bone tissue of long bones with a new device. A described technique is for restoring the length of limbs in defects by lengthening with a new device.